A Rare Case of Spontaneous Heterotopic Pregnancy at 12 weeks of Gestation Following Natural Conception With Literature Review - Wang F; Xu Y; Dong X; Jiang P; Yu QQ (International Journal of Women's Health)
Fei Wang,1,* Yuting Xu,1,* Xin Dong,2 Pei Jiang,3 Qing-Qing Yu4 1Department of Gynecology, Jining No.1 People’s Hospital, Jining, People’s Republic of China; 2Department of Ultrasonography, Jining No.1 People’s Hospital, Jining, People’s Republic of China; 3Translational Pharmaceutical Laboratory, Jining NO.1 People’s Hospital Jining, People’s Republic of China; 4Clinical Research Center, Jining NO.1 People’s Hospital, Jining, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qing-Qing Yu, Clinical Research Center, Jining No.1 People’s Hospital, Jining, People’s Republic of China, 272011, Email yuqingqing_lucky@163.com Pei Jiang, Translational Pharmaceutical Laboratory, Jining No.1 People’s Hospital, Jining, 272011, People’s Republic of China, Email jiangpeicsu@sina.comBackground: Spontaneous heterotopic pregnancy is an uncommon and possibly serious problem characterized by maternities at unique implantation sites, with only one occurring in the intrauterine cavity. Its incidence is approximately 1 in 30,000 natural pregnancies, posing significant threats to maternal health. The complexity of clinical and laboratory findings complicates its diagnosis, necessitating a high index of suspicion for prompt intervention.Case Presentation: We reported the case of a 36-year-old woman diagnosed with heterotopic pregnancy at 12 weeks of gestation following spontaneous conception, who presented with severe abdominal pain. Initial beta-human chorionic gonadotropin (β-hCG) levels were 57,278.00 mIU/mL. Transvaginal ultrasound (TVUS) revealed a single live fetus in the uterus, estimated at 12 weeks and six days, alongside a thick-walled cystic structure in the right ovary and an irregular hypoechoic mass inferior to the right ovary. An urgent laparoscopic salpingectomy was performed under general anesthesia, revealing a distended right fallopian tube (3.5 cm) with a thickened appearance, bluish-purple discoloration, and a 2 mm rupture with active bleeding surrounded by clots. Histopathological examination confirmed ectopic pregnancy. Postoperative β-HCG levels were 49,213 mIU/mL and 57,577 mIU/mL on the second and third days, respectively.Conclusion: Clinicians should maintain vigilance for heterotopic pregnancy, especially in the absence of infertility treatments or known risk factors. Lower quadrant abdominal or pelvic pain should prompt consideration of heterotopic pregnancy, as the presence of an intrauterine pregnancy does not exclude a concurrent ectopic pregnancy.Keywords: ectopic pregnancy, heterotopic pregnancy, laparoscopy, spontaneous pregnancy